2022
DOI: 10.3390/ma15227888
|View full text |Cite
|
Sign up to set email alerts
|

Review on Fluorescent Carbon/Graphene Quantum Dots: Promising Material for Energy Storage and Next-Generation Light-Emitting Diodes

Abstract: Carbon/graphene quantum dots are 0D fluorescent carbon materials with sizes ranging from 2 nm to around 50 nm, with some attractive properties and diverse applications. Different synthesis routes, bandgap variation, higher stability, low toxicity with tunable emission, and the variation of physical and chemical properties with change in size have drawn immense attention to its potential application in different optoelectronics-based materials, especially advanced light-emitting diodes and energy storage device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…19 The assembly of the N-GQD/GH/CF positive electrode and the GH/CF negative electrode into an asymmetric flexible fiber supercapacitor is shown schematically. 90 Fig. 20 (a-f ) Asymmetric N-GQD/GH/CF/GH/CF FFSC electrochemical performance on a two-electrode system in an H 2 SO 4 /PVA electrolyte.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…19 The assembly of the N-GQD/GH/CF positive electrode and the GH/CF negative electrode into an asymmetric flexible fiber supercapacitor is shown schematically. 90 Fig. 20 (a-f ) Asymmetric N-GQD/GH/CF/GH/CF FFSC electrochemical performance on a two-electrode system in an H 2 SO 4 /PVA electrolyte.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[1][2][3][4] The use of carbon and its derivatives, such as reduced graphene oxide (rGO) and graphene quantum dots (GQDs), in supercapacitor technology is one eld of study that has showed promise. 5,6 Due to their distinctive characteristics, such as their high electrical conductivity, wide specic surface area, and ease of modication, GQDs and rGO are well suited for energy storage applications. 7,8 Unfortunately, there are various difficulties and issues with GQDs and rGO in supercapacitor technology, such as low energy density, a limited working voltage, and nding costeffective synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors are used in a wide range of energy storage applications, such as portable electronic devices [ 1 , 2 ] and electric vehicles [ 3 , 4 , 5 ], thanks to their high power density, expanded cycle life, and fast charging speed. In an electric double-layer capacitor (EDLC), the electrode is made of porous carbon materials with high specific surface area which leads to a high capacitance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%